2016
DOI: 10.1111/ped.13174
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of infant anemia in the perinatal period

Abstract: Infant nutrition method was the most significant factor related to anemia in late infancy. Infants with low umbilical cord blood hemoglobin are more likely to develop anemia in late infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…The longer the infant is breastfed, the worse the severity of childhood anemia [ 18 ]. In 2017, Hirata et al in Japan showed that the infant feeding method was the most significant risk factor for IDA, followed by exclusive breastfeeding, and partial breastfeeding, with formula feeding having the lowest risk [ 19 ]. A cross-sectional study in Thailand reported that if mothers received adequate nutritional supplements, including iron, during pregnancy and lactation, exclusive breastfeeding up to 6 months should be advocated due to its substantial health benefits, particularly for anemia [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The longer the infant is breastfed, the worse the severity of childhood anemia [ 18 ]. In 2017, Hirata et al in Japan showed that the infant feeding method was the most significant risk factor for IDA, followed by exclusive breastfeeding, and partial breastfeeding, with formula feeding having the lowest risk [ 19 ]. A cross-sectional study in Thailand reported that if mothers received adequate nutritional supplements, including iron, during pregnancy and lactation, exclusive breastfeeding up to 6 months should be advocated due to its substantial health benefits, particularly for anemia [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 The US Department of Health and Human Services has set a target of reducing ID by 10% in children aged 1-2 years by 2020. 7 There are only a few reports from small cohorts on the ID and IDA prevalence in Japan, [8][9][10][11] and ID and IDA have not received adequate attention from Japanese academic societies and government agencies.…”
mentioning
confidence: 99%
“…Aunque las guías actuales de suplementación con hierro del MINSA indican que la suplementación preventiva debe realizarse por el lapso de 12 meses continuos en los niños de 6 a 36 meses de edad(26), consideramos que, para el caso de comunidades como las estudiadas, la suplementación debería mantenerse de manera continua durante los primeros 24 meses, como lo recomendaba antes la OMS(27), inclusive hasta los 36 meses de vida y debería comenzar aún antes de la ablactancia, a partir del mes de edad, tal como el MINSA lo recomienda para grupos de riesgo especiales como los niños de bajo peso al nacer y los prematuros(26). Por otra parte, el adecuado control del embarazo y la suplementación con hierro de las gestantes debería ser una prioridad en estos ámbitos, así como la implementación de otras medidas tales como el pinzamiento tardío del cordón umbilical durante el parto, la desparasitación de los niños, la consejería en temas nutricionales y el seguimiento y vigilancia comunitaria (4, 22, 28, 29).…”
Section: Discussionunclassified